Efeitos dos agrotóxicos diuron e carbofuran, isolados e em mistura, sobre organismos aquáticos e avaliação de risco ecológico - Mansano, Adrislaine da Silva (Universidade Federal de São Carlos, 2016)
The aim of this study was to evaluate the effects of diuron and carbofuran, isolated and mixed, on Raphidocelis subcapitata, Paramecium caudatum and Ceriodaphnia silvestrii and carry out a preliminary risk assessment of these pesticides for Brazilian water bodies. For this, acute and chronic toxicity tests were performed with individual compounds and in combination, in its standard form and commercial formulations. The results showed that in individual action, these pesticides significantly inhibited the R. subcapitata population growth and caused physiological (chlorophyll a content) and morphological (complexity and cell size) changes in the cells. For this alga, the toxicity of standard active ingredients and their commercial formulations showed no significant differences. For the protozoan P. caudatum, acute toxicity tests evidenced an increase of mortality with increasing exposure time for the selected compounds. Moreover, these pesticides caused a significant decrease in population growth, number of generations and biomass of P. caudatum. The toxicity of standard diuron and its commercial formulation was similar for this protozoan, while commercial carbofuran was more toxic than its standard form, suggesting a synergistic interaction with “inert” ingredients. In contrast, for the cladoceran C. silvestrii, acute toxicity tests showed that diuron commercial product was 7.2 times more toxic than its standard active ingredient, whereas for carbofuran, commercial product was 1.5 times less toxic than its standard active ingredient. Regarding chronic toxicity of diuron herbicide, both standard and commercial form caused hormetic effects on fertility of C. silvestrii female. Carbofuran significantly reduced the reproduction of C. silvestrii at concentrations from 0.38 μg L-1 onwards. The tropical species C. silvestrii was more sensitive to these pesticides than cladocerans commonly used in temperate regions, and in addition, for carbofuran, this species was the most sensitive organism already tested (EC50-48h = 0,86 μg L-1). According to the toxicity tests results of diuron and carbofuran mixtures, acute and chronic exposures on all selected test organisms caused significant deviations from the toxicity predicted by Concentration Addition and Independent Action reference models. For P. subcapitata, data indicated the occurrence of synergism in the mixture of these compounds, especially when diuron is the dominant chemical in combination. For P. caudatum, dose ratio dependent deviation (synergism caused by carbofuran and antagonism caused by diuron) was observed in acute exposure and deviation for antagonism was verified for population growth at sublethal concentrations of the standard compounds mixtures. For C. silvestrii, antagonism was observed in low doses and synergism at high doses, predominating synergism in acute exposures of standard pesticides mixtures, while for reproduction the deviation for antagonism was found. The commercial product mixtures of diuron and carbofuran showed significantly different effects and more severe than the standard compounds mixtures for P. caudatum and C. silvestrii. Therefore, diuron and carbofuran mixture can interact and cause toxic responses different from those predicted for individual compounds. According to the concentrations found in water bodies in Brazil, these compounds can cause direct and indirect toxic effects on communities of algae, protozoa and cladocerans and may change the structure and functioning of aquatic ecosystems. In a preliminary risk assessment of these pesticides, risk quotients were larger than 1, indicating that diuron and carbofuran represent potential ecological risks to Brazilian water bodies. Given the above, it is concluded that the pesticides studied alone and in combination, caused toxicity to test organisms and represent potential ecological risk for aquatic environments, which suggests the implementation by the regulatory agencies of more stringent measures for the use of pesticides to improve the protection of aquatic biota.
Keywords: Ecotoxicologia; Raphidocelis subcapitata; Paramecium caudatum; Ceriodaphnia silvestrii; Diuron Nortox® 500 SC; Furadan® 350 SC; Ecotoxicology; Raphidocelis subcapitata; Paramecium caudatum; Ceriodaphnia silvestrii; Diuron Nortox® 500 SC; Furadan® 350 SC; CIENCIAS BIOLOGICAS